1999
DOI: 10.1523/jneurosci.19-14-06191.1999
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Hippocampus and Medial Septum during Sharp Waves and Theta Oscillation in the Behaving Rat

Abstract: The medial septal region and the hippocampus are connected reciprocally via GABAergic neurons, but the physiological role of this loop is still not well understood. In an attempt to reveal the physiological effects of the hippocamposeptal GABAergic projection, we cross-correlated hippocampal sharp wave (SPW) ripples or theta activity and extracellular units recorded in the medial septum and diagonal band of Broca (MSDB) in freely moving rats. The majority of single MSDB cells (60%) were significantly suppresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
177
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 185 publications
(193 citation statements)
references
References 60 publications
15
177
0
1
Order By: Relevance
“…As is the case with thalamo-cortical spindles in which corticothalamic feedback serves as a synchronizer, hippocampal feedback to the medial septum is crucial for producing widespread synchrony (King et al, 1998). However, the hippocamposeptal feedback path is established by long-range GABAergic interneurons (Sik et al, 1994;Dragoi et al, 1999;Gulyas et al, 2003). The septal and intrahippocampal pathways produce a current source in the CA1 pyramidal layer and a sink in the stratum radiatum of CA1.…”
Section: Slow (<1 Hz) Rhythms-mirceamentioning
confidence: 99%
“…As is the case with thalamo-cortical spindles in which corticothalamic feedback serves as a synchronizer, hippocampal feedback to the medial septum is crucial for producing widespread synchrony (King et al, 1998). However, the hippocamposeptal feedback path is established by long-range GABAergic interneurons (Sik et al, 1994;Dragoi et al, 1999;Gulyas et al, 2003). The septal and intrahippocampal pathways produce a current source in the CA1 pyramidal layer and a sink in the stratum radiatum of CA1.…”
Section: Slow (<1 Hz) Rhythms-mirceamentioning
confidence: 99%
“…These hippocampo-septal projection cells receive convergent input from large numbers of hippocampal principal cells (Tóth et al, 1993). Hippocampal activity may thus inhibit the septum; indeed, both fimbria stimulation (McLennan and Miller, 1974) and hippocampal sharp waves (Dragoi et al, 1999) were shown to inhibit neuronal activity in the medial septum.…”
Section: Acetylcholine and Learning Dynamicsmentioning
confidence: 99%
“…In this respect it is noteworthy that the few studies addressing the function of the hippocampo-medioseptal pathway were performed in anaesthetized rats, and did not characterize the neurons responding to hippocampal input (McLennan and Miller, 1974;Dragoi et al, 1999). Moreover, the clearest effects of hippocampal influence on septal activity were observed during hippocampal sharp waves, rather than REM-associated theta (Dragoi et al, 1999).…”
mentioning
confidence: 99%
“…These numerous sources of theta generators are believed to be coordinated by the reciprocal connections between the septum and hippocampus (23), but the nature of this spatial-temporal coordination is not well understood (24). Both cholinergic and GABAergic neurons, and a small fraction of VGlut2 immunoreactive neurons (25), are believed to play a critical role in such global coordination (26,27). Although GABAergic neurons of the MS were demonstrated to be entrained at theta frequency, identified cholinergic neurons did not show theta-related discharge pattern (28,29).…”
mentioning
confidence: 99%